The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/molbev/msac120
|View full text |Cite
|
Sign up to set email alerts
|

How Placenta Promotes the Successful Reproduction in High-Altitude Populations: A Transcriptome Comparison between Adaptation and Acclimatization

Abstract: As the best adapted high altitude population, Tibetans feature a relatively high offspring survival rate. Genome-wide studies have identified hundreds of candidate SNPs related to high altitude adaptation of Tibetans, although most of them have unknown functional relevance. To explore the mechanisms behind successful reproduction at high altitudes, we compared the placental transcriptomes of Tibetans, sea level Hans (SLHan), and Han immigrants (ImHan). Among the three populations, placentas from ImHan showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…We first examined expression within an a priori gene set that included genes hypothesized to be relevant to altitude adaptation, placental physiology, and fetal growth outcomes in humans (43)(44)(45)(46)(47)(48)(49)(50)(51). Across its evolution, placentas have repeatedly co-opted genetic toolboxes and gene duplications from other tissues (52-54), and thus we might not expect there to be substantial overlap at the gene level between human and deer mouse gene sets that are associated with fetal growth outcomes and hypoxia responses.…”
Section: Genes Involved In Gestational Hypoxia and High Elevation Ada...mentioning
confidence: 99%
See 3 more Smart Citations
“…We first examined expression within an a priori gene set that included genes hypothesized to be relevant to altitude adaptation, placental physiology, and fetal growth outcomes in humans (43)(44)(45)(46)(47)(48)(49)(50)(51). Across its evolution, placentas have repeatedly co-opted genetic toolboxes and gene duplications from other tissues (52-54), and thus we might not expect there to be substantial overlap at the gene level between human and deer mouse gene sets that are associated with fetal growth outcomes and hypoxia responses.…”
Section: Genes Involved In Gestational Hypoxia and High Elevation Ada...mentioning
confidence: 99%
“…After filtering, mapping, and feature D R A F T assignment, our analysis included an average of 29.5M reads from our junctional zone/decidua samples (Range: 16.2 -39.3M), and an average of 31.3M reads from our labyrinth zone samples (Range: a priori dataset generation and analysis. We compiled a priori genes of interest from the literature, including genes hypothesized to be relevant to altitude adaptation and protection of fetal growth in 787 humans as well as genes with empirical evidence for differential 788 expression among lowland and highland human populations in the 789 placenta (39,45). Neither (39) nor (45) associate gene expression 790 with fetal growth outcomes, but instead focus on genes are differ-791 entially expressed between highlanders (Tibetans or Andeans) and lowlanders and hypoxia sensitivity.…”
Section: Rnaseq Data Generation and Analysis Tissue Was Homogenized Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of hypoxia have been investigated in high-altitude pregnancies [22]. It has been shown that placental natural functions are strengthened for the well-adapted inhabitants of high altitude, representing a preserved relationship between the placenta and fetus [23]. However, short-time exposure to hypoxic conditions as a result of immigration to high-altitude places showed common hypoxic stress response [23].…”
Section: Introductionmentioning
confidence: 99%